2003
DOI: 10.1074/jbc.m210413200
|View full text |Cite
|
Sign up to set email alerts
|

Allosteric Modulation of Human P-glycoprotein

Abstract: The human multidrug transporter P-glycoprotein (Pgp, ABCB1) contributes to the poor bioavailability of many anticancer and antimicrobial agents as well as to drug resistance at the cellular level. For rational design of effective Pgp inhibitors, a clear understanding of its mechanism of action and functional regulation is essential. In this study, we demonstrate that inhibition of Pgp-mediated drug transport by cis-(Z) Cellular expression of human P-glycoprotein (Pgp), 1 the product of the MDR1 gene, confers r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
21
0

Year Published

2006
2006
2017
2017

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 88 publications
(25 citation statements)
references
References 39 publications
4
21
0
Order By: Relevance
“…Since fluoroaluminate traps both dinucleotide and trinucleotide at the catalytic site (37), the ability of cis-(Z)-flupentixol to regenerate [ 125 I]IAAP binding to fluoroaluminate-trapped Pgp indicates that irrespective of whether the low affinity state is generated by nucleotide hydrolysis (18,19) or by tight nucleotide binding (21), transition to the high affinity state can be induced by the modulator. An argument can be made that the recovery of 125 I]IAAP binding suggested no physical overlap between the interaction sites of the two (18,32). In this report, we demonstrate that in a catalytic transition state conformation of Pgp, which prevents binding of transport substrate […”
Section: Discussionmentioning
confidence: 71%
See 4 more Smart Citations
“…Since fluoroaluminate traps both dinucleotide and trinucleotide at the catalytic site (37), the ability of cis-(Z)-flupentixol to regenerate [ 125 I]IAAP binding to fluoroaluminate-trapped Pgp indicates that irrespective of whether the low affinity state is generated by nucleotide hydrolysis (18,19) or by tight nucleotide binding (21), transition to the high affinity state can be induced by the modulator. An argument can be made that the recovery of 125 I]IAAP binding suggested no physical overlap between the interaction sites of the two (18,32). In this report, we demonstrate that in a catalytic transition state conformation of Pgp, which prevents binding of transport substrate […”
Section: Discussionmentioning
confidence: 71%
“…These results suggested that the [ 125 I]IAAP site remains occluded in the vanadatetrapped conformation and only becomes accessible after a second hydrolytic event (28). We reported that thioxanthene-based Pgp modulators, such as flupentixols, allosterically interact with Pgp through a site that is functionally distinct from the site of substrate ([ 125 I]IAAP) recognition (32). In this study, we demonstrate that in the vanadatetrapped low affinity conformation of Pgp, the allosteric site remains accessible and responsive to allosteric modulation by cis-(Z)-flupentixol (Fig.…”
Section: Discussionmentioning
confidence: 92%
See 3 more Smart Citations